The Use of Code Switching Among Waiters in Restaurant and Bar Operations at Amber Resort-Selong Belanak Central Lombok - Ainul Yakin; Endang Sriwahyuni; Lalu Ahmad Zaki (Faculty of Economics and Business, University of Mataram, 2023)
The purpose of this study is to analyze what language elements are most widely used in code-switching among waiters at the Amber Beach Resort restaurant. The data collection methods used in this research include document study, field research, collecting data by recording respondents, and taking notes (Note Taking) on managers and F&B Service staff at Amber Beach Resort Restaurant. The results found that the language elements that experienced the most code switching were from Indonesian to English and Sasak language to English. Waiters/managers and other staff mostly use Indonesian to Indonesian elements.